Technical Skills and Competence of Sports Officiating Officials: Basis for an Action Plan (International Journal of Scientific Research and Management (IJSRM), 2023)
This research was conducted to determine the level of the technical skills and competence of sports officiating officials in schools division office of Escalante City during the School Year 2020-2021. Further, the study wanted to determine the level of the technical skills and competence of sports officiating officials when respondents are grouped and compared according to selected variables. Moreover, the result of the study also sought for an action plan. In view of the nature of the objectives of this study, the descriptive research design was used. A total of 82 sports officiating officials served as respondents of the study in the schools division office of Escalante City. The research instrument used in gathering data was a self-made questionnaire. To determine the profile of the respondents, data frequency and percentage were used. The study revealed that as assessed by the sports officiating officials when they are grouped according to the study’s variables, the results show a "high level" in all areas.Furthermore, the assessment of the level of technical skills of sports officiating officials in terms of areas indicated no significant difference when grouped and compared according to aforementioned variables. While the assessment on the level of competence of sports officiating officials in terms of areas of skills according to the level of accreditation and number of years as sports officiating officials indicated a significant difference and same is through in terms of area of training that all indicated with a significant difference when being grouped and compared according to aforementioned variables. Based on the findings of the study, the following relevant recommendations were advanced for consideration of those concerned: the findings of the study will be forwarded to the schools division office of Escalante City for them to be aware of the level of technical skills and competence of sports officiating officials. There is a strong need to improve certain areas in order that urgent and alternative measures can be planned and implemented. The division office can use the findings of this study in crafting interventions or proposing a plan of activities to satiate its policy lapses if there are any. School heads and supervisors in the schools division office of Escalante City may recommend doable interventions and propose a plan of activities via an action plan in order to formulate a viable roadmap to provide a clear guide to plans and programs to improve the level of technical skills and competence of sports officiating officials. Also, the proposed action plan must be considered in order to improve the said the level of technical skills and competence of sports officiating officials in the schools division office of Escalante City.